Decarbonizing methanol synthesis via low-carbon hydrogen: process simulation and techno-economic insights - Khawaja, Razan; Musa, Tagwa; Challiwala, Mohamed Sufiyan; El-Halwagi, Mahmoud M.; Elbashir, Nimir O. (Frontiers in Chemical Engineering, 2025)
Methanol synthesis is one of the most hydrogen-intensive chemical processes, making its decarbonization a critical step toward climate-aligned chemical production. In this study, Aspen Plus® process simulation and techno-economic assessment (TEA) were applied to evaluate and compare four hydrogen production configurations for natural-gas-based methanol synthesis with capacity of 5,000 tons/day: (i) a conventional partial oxidation (POx)- water-gas shift reaction (WGS) base case, (ii) advanced reforming of methane (ARM) with integrated CO2 utilization and multi-walled carbon nanotube (MWCNT) co-production, (iii) methane pyrolysis coupled with reverse water–gas shift reaction (RWGS), and (iv) POx supplemented with renewable hydrogen and oxygen from alkaline water electrolysis (AWE). Each configuration was assessed for syngas composition, carbon intensity (CI), capital and operating expenditures, net present value (NPV), internal rate of return (IRR), levelized cost of fuel (LCOF), and marginal abatement cost (MAC). Both ARM and Methane Pyrolysis + RWGS achieved net-negative CI (−0.47 and −0.57 kg CO2/kg MeOH, respectively), while AWE + POx reduced CI by 75% compared with the baseline and exhibited the lowest indirect emissions. ARM provided the highest profitability (NPV ≈ $20.2 B, IRR ≈ 118%/year) due to MWCNT revenues, whereas AWE-integrated delivered the lowest LCOF (≈$296/ton) and a negative MAC (≈−$137/ton CO2e), representing a cost-saving “no-regrets” decarbonization pathway. Methane pyrolysis and RWGS offered the deepest CO2 reduction but were more sensitive to natural gas and electricity prices. These results identify clear deployment niches: ARM in regions with robust carbon co-product markets, methane pyrolysis + RWGS where CO2 supply is abundant and valorization is feasible, and AWE-integrated where low-cost renewable electricity is accessible. Two-way sensitivity maps further delineate viability domains as a function of gas and methanol prices, providing a compact decision-support tool for investors.